Influence of sodium citrate on resistance of adherence of gypsum re-used | Influência do citrato de sódio sobre a resistência à aderência do gesso reutilizado - Araújo, Anderson Rubens Bispo de; Alves, Bruno Carlos de Araújo; Sarti, Francesco; Tavares, Yêda Vieira Póvoas (Revista Geama, 2016)
With the growth of construction, gypsum is widely used in Brazil. Nonetheless, its application as a coating generates large waste due to labor disqualified and the improper disposal. Because of this waste production which can reach 50% of all municipal solid waste, it was interesting in making a comparison between the adhesion strengths for mixtures of gypsum residue and the addition of retardant additive (sodium citrate). The objective of this research is to evaluate the influence of sodium citrate in the adhesive strength of the gypsum plaster with or without the addition of gypsum waste. Sodium citrate was inserted into the mixture in the proportion of 0.06% over the weight of gypsum. In the preparation of gypsum panels with and without residue and sodium citrate, it was waited to dry and followed NBR 13528 (2010) to evaluate the bond strength for each plaster section. The results demonstrate that sodium citrate interferes with the adhesive strength of the gypsum plus residue mixture. Even with a longer drying waiting-time, the adhesive strength is unchanged. Therefore, depending on the purpose of the coating, it should be have in mind for the reuse of gypsum residue on the handle retarder, as it can alter the bond strength interfering with the final quality.